Medium Frequency Physical Vapor Deposited Al2O3 and SiO2 as Etch-Stop-Layers for Amorphous Indium-Gallium-Zinc-Oxide Thin-Film-Transistors. (18th March 2015) - Nag, Manoj; Bhoolokam, Ajay; Steudel, Soeren; Chasin, Adrian; Maas, Joris; Genoe, Jan; Murata, Mitsuhiro; Groeseneken, Guido; Heremans, Paul
Abstract : In this work, we report on amorphous-Indium-Gallium-Zinc-Oxide (a-IGZO) thin-film transistor (TFT) with medium frequency physical vapor deposited (mf-PVD) etch-stop-layer (ESL). TFT with mf-PVD ESL show comparable characteristics such as field-effect mobility (μFE ), sub-threshold slope (SS −1 ) and current ratio (ION/OFF ) to the conventional plasma enhanced chemical vapor deposition (PECVD) ESL based TFT, however significant differences were observed in gate bias-stress stabilities. The TFTs with mf-PVD ESL showed lower threshold-voltage (VTH ) shifts compared to TFTs with PECVD ESL when stressed under a gate field of +/−1 MV/cm for duration of 10 4 seconds in dark and light conditions. We associate the better bias-stress stability of the mf-PVD ESL based TFT to better passivating properties and the low hydrogen content of the mf-PVD layer compared to PECVD layer.